Hambatan Akses Pelayanan Kesehatan Orang Cebol - Atik Triratnawati; Yauma Ayu Arista (Berita Kedokteran Masyarakat (BKM), 2019)
Barrier of health services access among dwarfishPurpose: Study describes how people with dwarfism seek access and the barriers of accessing healthcare services.Method: Participatory observation method with in-depth interviews among people with dwarfism, family, healthcare officers, midwives and the head village were used in this study. The location was in Sigedang Village, Kejajar District, Wonosobo Regency, Central Java for 2 months between  August-September 2017.Results: The study reveals stigma surrounding dwarfism in Sigedang society that dwarfism was hereditary. According to Sigedang people, abnormality was considered natural. Access to healthcare for people with dwarfism was limited. There were no efforts that has been made by either the village government nor the sub-district government for an increased prevention program for people with dwarfism in Sigedang village. People with dwarfism had limited information about healthcare services available for them. They must travel far to the city or across the regency just to reach the standard health facilities. Therefore, an increase of an integrated health access in Sigedang village is needed, especially for people with dwarfism.In addition, the study shows that health-seeking behavior of the locals was still influenced by the ancestors, where traditional medical practitioners played an important role. The awareness of people suffering from dwarfism and their community towards risk factors should be empowered.Conclusion: The absence of access to health services influenced the poor condition among people with dwarfism. They need empowerment from the local government, public health office and community to support their health service needs.